Local brain gyrification as a marker of neurological soft signs in schizophrenia - Hirjak, Dusan; Kubera, Katharina Maria; Wolf, Robert Christian; Thomann, Anne K.; Apondo, Sandra; Thomann, Philipp (Behavioural brain research, 2015)
Patients with psychiatric disorders of significant neurodevelopmental origin, such as schizophrenia and autism frequently experience genuine motor abnormalities, such as neurological soft signs (NSS). Previous MRI studies in patients with schizophrenia have shown that NSS are associated with abnormal cortical, thalamic and cerebellar structure and function. So far, however, no neuroimaging study focused on the role of the local gyrification index (LGI) in the pathophysiology of NSS. This study sought to explore the relationship between NSS and folding patterns of the cerebral cortex that are thought to be established during early brain development. In this study, whole brain high-resolution magnetic resonance imaging (MRI) at 3 Tesla was used to investigate the LGI in 33 patients with recent-onset schizophrenia. Cortical reconstruction was performed with the Freesurfer image analysis suite. NSS were examined on the Heidelberg Scale and related to LGI. Age, gender, years of education and medication were considered as potential confounding variables. In summary, higher NSS scores were positively associated with morphological changes of LGI predominantly in parietal and occipital areas. Our results confirm the hypothesis of a significant relationship between LGI changes and the NSS expression in schizophrenia. Investigation of LGI may help to explain subtle motor symptoms such as NSS in schizophrenia.